First-order grain boundary transformations in Au-doped Si: Hybrid Monte Carlo and molecular dynamics simulations verified by first-principles calculations. (1st January 2019) - Hu, Chongze; Luo, Jian
Abstract: Hybrid Monte Carlo and molecular dynamics simulations (hybrid MC/MD) reveal the occurrence of first-order phase-like adsorption transformations in Au-doped Si twist grain boundary (GB) at low temperatures, which become continuous at high temperatures above a GB critical point. The predicted first-order GB transformations from nominally "clean" GBs to bilayer adsorption of Au are supported by a prior experiment. The hexagonal Au adsorption pattern predicted by the hybrid MC/MD simulation is further verified by first-principles calculations. Differential charge density maps indicate that strong charge transfer at the Au-doped Si GB. A GB complexion (interfacial phase) diagram is computed. Graphical abstract: Unlabelled Image